Melaka Sustainability Outlook Diagnostic : Overview Report - Pathway to Urban Sustainability - Global Platform for Sustainable Cities; World Bank (World Bank, Washington, DC, 2019)
Melaka State, situated roughly halfway between Kuala Lumpur and Singapore, has unique importance in the global dialogue around the sustainability of our shared urban future. At Melaka’s heart is its historic urban center, a UNESCO World Heritage Site (WHS) strategically located along the Strait of Malacca, one of the world’s busiest shipping routes and a link between the two largest countries by population, China and India. Melaka has taken significant steps toward realizing a more sustainable urban growth trajectory, including becoming a member of global platform for sustainable cities (GPSC) when the platform was launched in 2016. In 2017, GPSC initiated the sustainability outlook diagnostic with the United Nations Industrial Development Organization (UNIDO) and the Malaysian industry-government group for high technology (MIGHT) to assist Melaka State in achieving the level of urban sustainability to which it aspires. This detailed assessment covers six dimensions of sustainability. Each report provides significant insight into different aspects of Melaka’s sustainability trajectory and highlights key areas for improvement.